Plasma amino-terminal pro–B-type natriuretic peptide quantification in hypertrophic cardiomyopathy - Arteaga, Edmundo; Araujo, Aloir Queiroz; Buck, Paula; Ianni, Barbara Maria; Rabello, Rogerio; Mady, Charles (The American heart journal, 2005)
Plasma B-type natriuretic peptide (BNP) is a sensitive functional marker in heart disease including hypertrophic cardiomyopathy (HCM). The utility of plasma amino-terminal pro-BNP (NT-proBNP) quantification in heart disease has been investigated, but there are no published data regarding this test in HCM. Plasma NT-proBNP was assessed in 71 patients with HCM and in 40 healthy subjects. Symptomatic status was assessed according to the New York Heart Association classification. M-mode and Doppler echocardiographic data were obtained in all patients and healthy subjects to study their correlations and comparisons (Spearman and Mann-Whitney tests). Median NT-proBNP was 848 pg/mL in patients and 28 pg/mL in the control group ( P < .0001). Patients in New York Heart Association functional class I/II had a median NT-proBNP of 669 pg/mL as compared with 3357 pg/mL for patients in class III/IV ( P < .0001). Amino-terminal pro-BNP levels correlated positively with left atrial diameter ( r = 0.40, P = .0005), septal thickness ( r = 0.35, P = .002), and mitral flow velocity/mitral annulus velocity (E/Ea) ratio ( r = 0.42, P < .0001). There was a weak correlation with obstruction ( r = 0.23, P = .05), and a significant difference in the medians was observed between obstructive (1651 pg/mL) and nonobstructive (669 pg/mL) HCM groups ( P = .01). Patients with Doppler E/Ea ratios ≥10 had higher NT-proBNP levels than patients with E/Ea <10 ( P < .0001). Multivariate analysis showed that NT-proBNP correlated independently with left atrial diameter ( P < .01), hypertrophy ( P < .01), and E/Ea ( P < .01). In HCM, plasma NT-proBNP levels are elevated and correlate positively with symptoms of heart failure, hypertrophy severity, and Doppler echocardiographic signs of left ventricular diastolic dysfunction. Further studies are necessary to assess the usefulness of the test in clinical practice and its role as a prognostic marker.